An experimental study on the influence of incorporating lap or forging (GPW) splices on the cyclic performance of RC columns. (15th August 2021) - Kheyroddin, Ali; Rouhi, Sina; Dabiri, Hamed
Highlights: Four RC columns with non-spliced, lap spliced and forging spliced bars were tested. Cyclic performance of RC columns under cyclic and axial loads was investigated. Hysteresis curves and crack propagations and failure mechanisms were analyzed. Seismic parameters including ductility, absorbed energy, stiffness, curvature and curvature ductility were evaluated. An equation was proposed for calculating plastic hinge length. Abstract: Bar splices play an important role on the performance of RC structures by transferring loads from one bar to another. Therefore, applying an appropriate method to achieve satisfactory stress transmission has become a major concern for structural designers. In the present study, the application of lap and forging splice methods in RC columns is evaluated experimentally. Four 1/3 scale RC columns were fabricated and examined under cyclic and axial loads: the reference column with non-spliced bars, one specimen with lap splices at the middle of column and two other specimens with forging splices at two different positions of longitudinal bars. Force-displacement hysteresis curves and crack propagation of the specimens are presented and discussed. Moreover, the specimens are compared together in terms of ductility, absorbed energy, stiffness and curvature to find out the influence of applying forging splice method. An equation is also proposed to calculate plastic hinge length of RC columns. Results indicated that using forging splices either at the middle or at the bottom of columns can increase displacement ductility, curvature ductility and plastic hinge length while lap splices can decrease mentioned seismic parameters. Moreover, incorporating forging splices at the bottom of columns may increase stiffness and ultimate moment. Overall, it was concluded that forging splices can be considered as a reliable method for bar splicing under cyclic and axial loads.